Enantioselective Aldol Addition of Acetaldehyde to Aromatic Aldehydes Catalyzed by Proline-Based Carboligases - Saifuddin, Mohammad (ACS Catal, 2020)
[Image: see text] Aromatic β-hydroxyaldehydes, 1,3-diols, and α,β-unsaturated aldehydes are valuable precursors to biologically active natural products and drug molecules. Herein we report the biocatalytic aldol condensation of acetaldehyde with various aromatic aldehydes to give a number of aromatic α,β-unsaturated aldehydes using a previously engineered variant of 4-oxalocrotonate tautomerase [4-OT(M45T/F50A)] as carboligase. Moreover, an efficient one-pot two-step chemoenzymatic route toward chiral aromatic 1,3-diols has been developed. This one-pot chemoenzymatic strategy successfully combined a highly enantioselective aldol addition step catalyzed by a proline-based carboligase [4-OT(M45T/F50A) or TAUT015] with a chemical reduction step to convert enzymatically prepared aromatic β-hydroxyaldehydes into the corresponding 1,3-diols with high optical purity (e.r. up to >99:1) and in good isolated yield (51–92%). These developed (chemo)enzymatic methodologies offer alternative synthetic choices to prepare a variety of important drug precursors.